Challenges of green electricity generation in Algeria to achieve the 2030-target - Boukhalkhal, Naceur; Rahmani, Maamar; Teggar, Mohamed (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE Département de génie mécanique, 2023)
in this work , we are talking about the increasing demand for energy day by day, with industrialization and the globalization of trade, especially with the spread of local equipment. This increase was mainly covered by the over-exploitation of fossil (non-renewable) energy sources. In the face of environmental requirements and the danger of depleting fossil fuels, the challenge is to find clean and renewable energy sources, such as solar, thermal and wind energy, and to find prospects commensurate with these energies. The city of Laghouat had a share of the renewable energies programs, as the results of the studies confirmed the possibility of applying them on the ground due to its location and suitable climate, Laghouat is known for its abundant sunlight and growing demand for sustainable energy sources.
Option : Renewable energies